Analisis Etnografi Virtual Tentang Proses Komunikasi Kesehatan Ibu dan Anak dalam Whatsapp Group “Tentang Anak” - Ditha Prasanti; Sri Seti Indriani (MediaTor (Jurnal Komunikasi), 2019)
It was starting from the author’s interest in mothers who are both urban women and put forward the concept of health literacy about care, healing, and health conditions of their children, if their children experience illness.. The purpose of this study is to describe the process of health communication that occurs in whatsapp group “Tentang Anak”; the topic of conversation conducted in whatsapp group “Tentang Anak”; and communication barriers that occur during the health communication process. This study uses a qualitative approach with virtual ethnographic methods. The results of the study showed that the ongoing health communication process included the search by the mother for the health information about their children in whatsapp group “Tentang Anak”. The topic of discussion is about information of healthy lifestyles for children, child development, child care, and child healing techniques when experiencing any pain. The communication barriers in the health communication process are personal obstacles, educational barriers, and time constraints.